Relationships between talent development environments and mental toughness: The role of basic psychological need satisfaction - Li, C.; Martindale, R.; Sun, Y. (Journal of Sports Sciences, 2019)
Although the talent development environment and mental toughness are critical for athletes to realise their athletic potential, there is a dearth of literature on whether the talent development environment can enhance mental toughness among those athletes who are identified with athletic potential (i.e., talented athletes). Drawing on self-determination theory (Deci & Ryan, 2000), this research examined the relationships between the talent development environment, basic psychological needs satisfaction and mental toughness. Talented athletes (n = 261) completed a survey measuring key features of the talent development environment, needs satisfaction and mental toughness. The results of structural equation modelling indicated that three environmental factors (i.e., long-term development focus, holistic quality preparation and communication) were positive predictors of needs satisfaction, which then positively predicted mental toughness. The talent development environment may be considered for promoting talented athletes` mental toughness.